Research progress on Alpinia oxyphylla in the treatment of diabetic nephropathy - Wang, Jing; Wang, Xiaomin; Ma, Tianpeng; Xie, Yiqiang (Frontiers in Pharmacology, 2024)
Diabetic nephropathy (DN) constitutes a major microvascular complication of diabetes and is a primary cause of mortality in diabetic individuals. With the global rise in diabetes, DN has become an urgent health issue. Currently, there is no definitive cure for DN. Alpinia oxyphylla, a Chinese herbal medicine traditionally used, exhibits a wide range of pharmacological effects and is frequently used in the prevention and management of DN. This paper offers an extensive review of the biological mechanisms by which Alpinia oxyphylla delivers therapeutic advantages in DN management. These mechanisms include activating podocyte autophagy, regulating non-coding RNA, modulating gut microbiota, alleviating lipotoxicity, counteracting oxidative stress, and diminishing inflammatory responses, underscoring the therapeutic potential of Alpinia oxyphylla in DN treatment.